Evaluating the safety and efficacy of the leukotriene receptor antagonist montelukast as adjuvant therapy in obese patients with type 2 diabetes mellitus: A double-blind, randomized, placebo-controlled trial - El-Khateeb, Eman; El-Berri, Eman I.; Mosalam, Esraa M.; Nooh, Mohamed Z.; Abdelsattar, Shimaa; Alghamdi, Amira M.; Alrubia, Sarah; Abdallah, Mahmoud S. (Frontiers in Pharmacology, 2023)
Background: Type 2 diabetes mellitus (T2DM) is common with obesity. Metformin is a first line therapy for this condition. However, it had only a minor impact on weight loss in some patients. Aim: This study aimed to evaluate the effectiveness, tolerability, and safety of montelukast add-on therapy to metformin in obese diabetic patients. Methods: One hundred obese diabetic adult patients were recruited and randomized into two equal groups. group1; received placebo plus metformin 2g/d and group2; received 2g/d metformin plus 10 mg/d montelukast. Demographic, anthropometric measurements (e.g., body weight, body mass index (BMI) and visceral adiposity index), lipid profile, diabetes-control measures (fasting blood glucose, glycated hemoglobin (HbA1c), and homeostatic model assessment for Insulin Resistance (HOMA-IR)), adiponectin, and inflammatory markers (e.g., TNF-α, IL-6, and leukotriene B4) were assessed and reported for each group at the baseline and after 12 weeks of treatment. Results: Both interventions significantly reduced all the measured parameters except adiponectin and HDL-C where the levels increased compared to baseline data (p<0.001). Montelukast group significantly improved all parameters compared to the placebo group (ANCOVA test p<0.001). The % changes in BMI, HbA1c, HOMA-IR, and inflammatory markers were 5%, 9%, 41%, and 5-30%, respectively in the placebo group compared to 8%, 16%, 58%, and 50-70%, respectively in the montelukast group. Conclusion: Montelukast adjuvant therapy was superior to metformin sole therapy in diabetes control and weight loss, most likely due to increased insulin sensitivity and anti-inflammatory properties. The combination was tolerable and safe within the study duration. Clinical Trial Registration: Clinicaltrial.gov (NCT04075110).